2021
DOI: 10.1007/s40820-021-00702-7
|View full text |Cite
|
Sign up to set email alerts
|

Spider Web-Inspired Graphene Skeleton-Based High Thermal Conductivity Phase Change Nanocomposites for Battery Thermal Management

Abstract: Phase change materials (PCMs) can be used for efficient thermal energy harvesting, which has great potential for cost-effective thermal management and energy storage. However, the low intrinsic thermal conductivity of polymeric PCMs is a bottleneck for fast and efficient heat harvesting. Simultaneously, it is also a challenge to achieve a high thermal conductivity for phase change nanocomposites at low filler loading. Although constructing a three-dimensional (3D) thermally conductive network within PCMs can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(51 citation statements)
references
References 64 publications
0
51
0
Order By: Relevance
“…A large amount of heat is generated during the charging/discharging process of electrochemical energy storage devices, which causes a rapid degradation of capacity and thermal runaway [ 13 , 211 , 212 ]. When Li-ion battery and supercapacitor are operated at high temperature, the softening of polymer separator is possible to cause electrical short circuit [ 213 ].…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A large amount of heat is generated during the charging/discharging process of electrochemical energy storage devices, which causes a rapid degradation of capacity and thermal runaway [ 13 , 211 , 212 ]. When Li-ion battery and supercapacitor are operated at high temperature, the softening of polymer separator is possible to cause electrical short circuit [ 213 ].…”
Section: Applicationsmentioning
confidence: 99%
“…When Li-ion battery and supercapacitor are operated at high temperature, the softening of polymer separator is possible to cause electrical short circuit [ 213 ]. Thus, thermally conductive films can also be used as the thermal management materials in energy storage devices to dissipate excess heat [ 13 , 214 ]. The research results demonstrated that BNNS composite membrane separator for Li-Ion battery can withstand an operating temperature up to 150 °C [ 213 , 214 ].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructing continuous thermal pathways is an efficient strategy to decrease ITR and enhance the through-plane TC [31][32][33]. Therefore, various methods, such as cutting-stacking, magnetic/electric fieldassisted alignment, and 3D printing, were studied to form vertical BN assembly to enhance the through-plane TC [34][35][36][37][38][39][40]. For example, Guo et al reported a stacking-cutting method to obtain vertical BN assembly relying on the transformation of alignment direction, and the as-prepared BN silicone composites showed a through-plane TC of 5.97 W m −1 K −1 at 60 wt% BN loading [41].…”
Section: Introductionmentioning
confidence: 99%
“…Constructing thermal conductive composites, by contrast, is attracting increasing attention because of its simplicity and effectiveness. 1–5…”
Section: Introductionmentioning
confidence: 99%